Social media and depression among young adults in Bangladesh: Patterns, predictors, and implications - Haque, Mst Rahnuma; Mondal, Md. Nazrul Islam; Haque, Moynul; Islam, Mohammad Mazharul; Sowmik, Md Hasanul Kabir; Parvin, Shela; Parvin, Mst Nadira (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Consequences have arisen about the impact of growing social media use on users’ psychological adverse well-being. Especially in young adults, it can increase feelings of loneliness, inadequacy, and social comparison. This study examines the role of social media in contributing to depression among young adults in Rajshahi city, Bangladesh. Methods: A cross-sectional study was conducted among 450 young adults in Rajshahi city, Bangladesh, using a structured questionnaire administered through face-to-face interviews and a purposive sampling technique. The Patient Health Questionnaire-9 (PHQ-9) was used to assess respondents’ depression status. Univariate and multivariate logistic regression were used to identify the factors of depression. Results: Over half of the respondents (57.8%) experienced depression, predominantly at moderate to severe levels, with higher rates observed among younger individuals (21–24 years) and females. Depression status was found to be significantly associated with respondents’ age, social media usage, time spent on social media, and following specific types of accounts such as celebrities or models, gaming, and animals or birds. Ultimately, Facebook usage (odds ratio (OR) 2.1; 95% confidence interval (CI) 0.9–5.0), WhatsApp usage (OR 0.5; 95% CI 0.3–0.7), and following accounts related to celebrities or models (OR 1.5; 95% CI 0.9–2.6), gaming (OR 1.9; 95% CI 1.0–3.6) were identified as significant factors of depression among young adults. Conclusion: More than half of young adults had depression. Social media usage, online time, and following accounts such as celebrities, models, and gaming are key contributors, emphasising the need for targeted mental health interventions, awareness campaigns, and digital literacy programs.